Creating and Appraising a Patient Educational Pamphlet for Migraine Sufferers - Raju, Nithya; Palaniappan, Divya; Hakkim, Femina; Palani, Gayathri; Thilagar, Jensilin Devakumari; Lalu, Jessly (Indian Journal of Pharmacy Practice)
Background: Migraine, an intricate genetic ailment, is identified by recurrent, intense headaches that typically impact one side of the head and frequently come with symptoms such as nausea and heightened sensitivity to light. Patient Education (PE) holds a crucial position in the management of migraines, serving as a fundamental element for both prevention and treatment. The objective of this study was to develop Patient Information Leaflets (PILs), assess their reception, and appraise their accessibility to individuals experiencing migraines. Materials and Methods: In this study, a patient information pamphlet was created and disseminated to 72 patients with incidence of migraine at a tertiary care hospital in Tamil Nadu. The patients’ understanding of the illness was evaluated using both the Flesch and Flesch-Kincaid Readability Test and the User Testing Readability Test. Results: We developed a Patient Information Leaflet (PIL) tailored for individuals suffering from Migraine. Subsequently, we evaluated its readability and user-friendliness. To measure readability, we employed the Flesch Reading Ease (FRE) score, where a score below 60 suggests difficulty for the general population. Our PIL attained an average FRE score of 73.9, classifying it as “relatively straightforward” to read. Conclusion: The research findings demonstrated that patients with migraine positively received the Patient Information Leaflets (PILs). Moreover, the study revealed a noteworthy enhancement in patient knowledge following their engagement with these PILs.
Keywords: Accessibility; Migraine; Patient Information Leaflet; prevention; Readability; Usability